Significance of application timing, formulation, and cytochrome P450 genotypic class on sweet corn response to dicamba. Issue 2 (21st March 2022) - Landau, Christopher A.; Bernards, Mark L.; Hager, Aaron G.; Williams, Martin M.
Abstract: Sweet corn ( Zea mays L.) tolerance to dicamba and several other herbicides is due to cytochrome P450 (CYP)-mediated metabolism and is conferred by a single gene ( Nsf1 ). Tolerance varies by CYP genotypic class, with hybrids homozygous for functional CYP ( Nsf1Nsf1 ) being the most tolerant and hybrids homozygous for mutant CYP alleles ( nsf1nsf1 ) being the least tolerant. The herbicide safener cyprosulfamide (CSA) increases tolerance to dicamba by stimulating the expression of several CYPs. However, the extent to which CSA improves the tolerance of different sweet corn CYP genotypic classes to dicamba is poorly understood. Additionally, the effect of growth stage on sweet corn sensitivity to dicamba is inadequately described. The objective of this work was to quantify the significance of application timing, formulation, and CYP genotypic class on sweet corn response to dicamba. Hybrids representing each of the three CYP genotypes ( Nsf1Nsf1, Nsf1nsf1, nsf1nsf1 ), were treated with dicamba or dicamba + CSA at one of three growth stages: V3, V6, or V9. Across all timings, the nsf1nsf1 hybrid was the least tolerant to dicamba, displaying 16% higher crop injury levels 2 wk after treatment and 2, 130 kg ha −1 lower ear mass yields compared with the Nsf1Nsf1 hybrid. The V9 growth stage was the most susceptible time for dicamba injury regardless of genotypic class, with 1.89 and 1, 750 kg ha −1 lower ear mass yields compared with the V3 and V6 application timings, respectively. The addition of CSA to dicamba V9 applications reduced the injury from dicamba for all three genotypic classes; however, it did not eliminate the injury. The use of Nsf1Nsf1 or Nsf1nsf1 sweet corn hybrids along with herbicide safeners will reduce the frequency and severity of injury from dicamba and other CYP-metabolized herbicides.